2017
DOI: 10.2807/1560-7917.es.2017.22.8.30469
|View full text |Cite|
|
Sign up to set email alerts
|

Mid-season real-time estimates of seasonal influenza vaccine effectiveness in persons 65 years and older in register-based surveillance, Stockholm County, Sweden, and Finland, January 2017

Abstract: Systems for register-based monitoring of vaccine effectiveness (VE) against laboratory-confirmed influenza (LCI) in real time were set up in Stockholm County, Sweden, and Finland, before start of the 2016/17 influenza season, using population-based cohort studies. Both in Stockholm and Finland, an early epidemic of influenza A(H3N2) peaked in week 52, 2016. Already during weeks 48 to 50, analyses of influenza VE in persons 65 years and above showed moderately good estimates of around 50%, then rapidly declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
18
2
Order By: Relevance
“…This may also partly explain the absence of influenza vaccine protection in Austria, where negative IVEs throughout the season were observed. This differs to data from other countries, where overall IVE's for this season of around 40% have been described (12)(13)(14)(15). Beyond viral genomic variation, birth cohort effects, prior vaccination in addition to the epidemic period may account for regional differences in IVE estimates (16,17).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…This may also partly explain the absence of influenza vaccine protection in Austria, where negative IVEs throughout the season were observed. This differs to data from other countries, where overall IVE's for this season of around 40% have been described (12)(13)(14)(15). Beyond viral genomic variation, birth cohort effects, prior vaccination in addition to the epidemic period may account for regional differences in IVE estimates (16,17).…”
Section: Discussioncontrasting
confidence: 81%
“…The proportion of this newly evolved subclade of the circulating viruses showed regional differences, depending on the start of the influenza season in the different European regions. In the northern parts of Europe, in Sweden and Finland, the influenza season 2016/17 started early in weeks 47/2016 to 49/2016 and peaked already in week 52/2016 (14). In these countries the genetic influenza surveillance revealed the presence of the genetic A(H3N2) subclade 3C.2a1 in 24% of the samples already at the beginning of the season, with an increase to 75% of the circulating viruses in the final weeks 52/2016 to 02/2017 (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available genetic characterisation data indicate that the circulating strains clustered to the same genetic lineages as the 2016/17 A(H3N2) inactivated vaccine virus strain, which was an A/Hong Kong/4801/2014 (H3N2)-like virus. Some authors have suggested that reduced VE may relate to the emergence of the genetic sub-clade 3C.2a1 [17,18]. We found a non-significantly lower VE for this sub-clade compared with the 3C.2a clade, although the antigenic characterisation data of circulating viruses remained limited, and there was no suggestion of mismatch based on the available information.…”
Section: Discussioncontrasting
confidence: 51%
“…A small number of studies have currently reported effectiveness in those aged 65 and above for the 2016/17 season, with the I-MOVE network also reporting a non-significant VE in the ≥ 65-year-olds of 23.4% (95% CI: − 15.4 to 49.1) [14], as did study teams from Sweden and Finland [17]. The observation of reduced VE in this vulnerable population may relate to the circulating virus strains, the vaccine itself and/or host factors.…”
Section: Discussionmentioning
confidence: 99%